LINC00261 Suppresses Cisplatin Resistance of Esophageal Squamous Cell Carcinoma Through miR-545-3p/MT1M Axis - Wang, Lijun; Wang, Xiaojun; Yan, Pengwei; Liu, Yatian; Jiang, Xuesong (Frontiers in Cell and Developmental Biology, 2021)
To improve the survival rate and cure rate of patients, it is necessary to find a new treatment scheme according to the molecular composition of (ESCC) in esophageal squamous cell carcinoma. Long non-coding RNAs (lncRNAs) regulate the progression of ESCC by various pathophysiological pathways. We explored the possible function of the lncRNA LINC00261 (LINC00261) on cisplatin (DDP) resistance of ESCC and its relative molecular mechanisms. In the study, we found that LINC00261 was downregulated in ESCC tissues, cell lines, and DDP-resistant ESCC patients. Besides, overexpression of LINC00261 not only inhibited cell proliferation, and DDP resistance but also promotes cell apoptosis. Further mechanistic research showed that LINC00261 sponged miR-545-3p which was negatively correlated with the expression of LINC00261. In addition, functional experiments revealed that upregulation of miR-766-5p promoted proliferation and enhanced DDP resistance. Subsequently, MT1M was testified to be the downstream target gene of miR-545-3p. Rescue experiments revealed that overexpression of MT1M largely restores miR-545-3p mimics-mediated function on ESCC progression. Our results demonstrate that the LINC00261 suppressed the DDP resistance of ESCC through miR-545-3p/MT1M axis.